A proposed Linux-Based Operating System specialized for library and information science students of the Philippines - Rosete, Carl Francis M.; Baylas, Bianca Rei T. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2012)
The creation of a specialized open source operating system or of an open source software application is a new and emerging thesis topic given the big impact of information technology to the field of Library and Information Science. Previous studies that have been conducted only focused on the development, analysis, usability, implementation and evaluation of open source software applications and the proposition implies but due to advancement in the field of information technology where automation and full customization is made available, such objectives are no longer difficult to achieve. Given these premises, the study focused on the proposition of creating a Linux-based operating system that is specialized for library and information science students of the Philippines. The study adapted a software development cycle model where careful planning and execution was done in order to achieve the main objectives of the study. The study had undergone four stages that included initial survey or investigation, analysis, design and development, and evaluation. All of which are carefully executed to produce a fully functional open source operating system.
The pilot testing and launching was done in UP School of Library and Information Studies (UP SLIS) wherein the students were asked to answer a survey about their preferred opens source applications. The preference of the students served as the basis for selection of what open source software applications were to be integrated in the proposed operating system. The initial survey also reflected the need to make certain software applications available for students because some of the open source applications were unheard of to most of the students. The technology exists and therefore it must be utilized to the advancement of the field. The types of software applications used in the survey were Desktop Managers or Environment, Web Browsers, General Purpose Application or Office Software Suites, Integrated Library System, Digital Repository Software, Content Management Systems, MARC Manipulation and Editing Software, Graphics and Image Editing Applications, Mock Up tools and other additional software that students need in this study. The previously mentioned categories were chosen for their contribution in the automation and advancement in the field of LIS. Having determined what were the most preferred open source applications, the design and creation of the operating system begun. Following a strict methodology, the Linux-based operating system was created using UBUNTU 11.10 Oneiric as the base operating system. The proposed operating system created was named LibrOS or Library Operating System version 1.0.
A task-based usability testing was also conducted to evaluate the performance of LibrOS wherein twenty LIS students of UP SLIS participated. The results show a very high success rate fir task completion and task performance and majority of the students found most of the task easy. However, most of the students had a hard time when it came to the tasks involving the use of digital repository software and database programming and management which was reflected from their task performance and time accumulated in the completion of the task. The results of the usability test showed that LibrOS is easy to use and understand. Also, the feedbacks on LibrOS were all positive and all of the students favored the use of such operating system giving regards on its key features.
It was concluded that the task time and degree of difficulty vary for each person in completing and performing the usability tasks wherein the results depended on the tasks given and the skill and familiarity of the person with the different software applications used. Obtaining s high success rate for task completion and task performance complements on the ease of use of the specialized operating system. Furthermore, the fact that only one failed one task as seen in the results and the eTask Performance part only shows that the specialized operating system is effective.
Recommendations included increasing the number of the sample population for more accurate results, the inclusion of other universities or colleges that are offering LIS courses to get a more sufficient data and a more accurate result, adding more open source software applications available as of today, further testing to improve the operating system and conducting further studies on customizing other Linux-based operating system to meet the growing needs in the field of library and information science.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Open source software -- Library applications; Linux device drivers (Computer programs).